PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK DENGAN MODEL DISCOVERY LEARNING PADA MATERI SEGIEMPAT DAN SEGITIGA KELAS VII SMP - Fauziah Tri Ulva (Jurnal Edukasi dan Penelitian Matematika, 2022)
Quadrilaterals and triangles are geometric materials that have many uses in everyday life. However, based on the data from Puspendik KEMENDIKBUD, only 36.68% of students answered the flat shape and circle area correctly, and 29.0%7 answered the question interpreting the combined area of the flat shape correctly. Learning tools take an important role in the learning process. Learning tools are one of the tools that teachers can use to help them achieve their learning goals. However, from the observation results at school, there is a discrepancy between the learning tools developed by the teacher and the learning process carried out in the classroom, and it is meaningful for the students to positively feel their concepts and knowledge. This research have purpose to advance learning device based on a scientific approach using a discovery learning model. This reserach uses the Plomp method, which consists of stages. (1) Preliminary phase which is analyze of needss, student, curriculumand concept), (2) Prototyping phase which is including design the product, self-evaluation, validation by expert, one on one evaluation, and small group Evaluation, (3) Evaluation Phase, which was performed in a large group (field test), but in this study only up to the small group evaluation phase. The result of this research was obtained from the results of interviews and surveys. The results of the analyze of the obtained data show that learning devices based on a scientific approach based on the developed discovery learning model are very effective at an average rate of 92.32% and very practical at a rate of 93.36% of students response. It also got  average 86.61% for practical by teachers' responese. From this, we can conclude that the resulting learning tools are effective and practical.Keywords __ Discovery learning, Learning, Plomp, Scientific approach